Influence of intercritical annealing temperature on TRIP/TWIP effect of retained austenite and tensile deformation mechanism of IQ&P steel - Zhang, Shaolong; Zhou, Wen; Hu, Feng; Wu, Kaiming; Yershov, Serhii (Journal of materials research and technology, 2024)
The aim of this study was to investigate the effects of intercritical annealing temperature on stability of retained austenite and tensile deformation mechanism of intercritical annealing quenching and partitioning (IQ&P) steels. By varying the intercritical annealing temperatures (700 °C and 750 °C), the following results were observed. The microstructure of experimental steels was examined by scanning electron microscopy, X-ray diffraction, and transmission electron microscope. With the decrease of intercritical annealing temperature from 750 °C to 700 °C, the content of retained austenite is doubled, and the microstructure is obviously refined. The mechanical properties of the test steel were tested by tensile test. The results demonstrate that the sample annealed at 700 °C showed the best product of tensile strength and elongation, which was above 34 GPa⋅% (ultimate tensile strength: 1016 MPa, total elongation: 33.5%). The fracture structure and morphology of the tensile specimens were examined to explore the key factors affecting the strength and plasticity of IQ&P steel. During the tensile process, the specimens annealed at lower temperatures maintained a better Kurdjumov-Sachs orientation relationship between the γ and α phases. In addition, the combination of a uniform distribution of microscopic stress and strain, a smaller difference in hardness between the phases and increased activation of multiple slip systems allows a greater amount of retained austenite in the low-temperature annealed specimens to be continuously subject to the transformation-induced plasticity (TRIP) and twinning-induced plasticity (TWIP) effect during the tensile process. The refinement of the microstructure and retained austenite grains could occur TRIP and TWIP effects in a more sustainable way, ultimately leading to more excellent comprehensive mechanical properties of the 700 °C annealed test steels.